A COMPARATIVE ANALYSIS OF CURRICULUM MANAGEMENT EFFECTIVENESS IN CLASSICAL, MODERN AND CONTEMPORARY ISLAMIC EDUCATION - Ardyanti, Yefi; Yudha Bahri , M. Farid; Khadijah , Ifah; Suherman , Usep (Sekolah Tinggi Agama Islam Al Hidayah Bogor, 2026)
Curriculum management in Islamic education is a strategic component in navigating contemporary educational challenges, technological shifts, and the evolving needs of 21st-century learners. While classical, modern, and contemporary curriculum models have been widely implemented, limited empirical research offers a comparative analysis of their managerial effectiveness in improving student outcomes. Purpose of the Study: This study aims to compare the effectiveness of three curriculum management approaches—classical, modern, and contemporary—in enhancing student academic achievement and motivation, and to evaluate their contextual alignment with current educational demands. Method: Adopting a quantitative approach with a comparative design, data were collected from 68 students enrolled in three Islamic educational institutions in Bandung, each representing one curriculum model. A closed-ended questionnaire using a four point Likert scale was administered, and data were analyzed using the Kruskal-Wallis test followed by Bonferroni-adjusted Pairwise Comparisons due to the non normal distribution of data. Results: The findings indicate that the contemporary curriculum management model demonstrated the highest level of perceived effectiveness (mean = 3.50), followed by the modern model (mean = 3.25) and the classical model (mean = 2.93), with statistically significant differences among the groups (p < 0.05). Conclusion: These results emphasize the importance of developing an integrative and contextually responsive curriculum management approach a one that remains grounded in Islamic values while adapting to modern pedagogical and technological demands in to improve the quality and sustainability of Islamic education in a holistic manner.